The Effectiveness of Bio-enzymes Made from Fruit Waste and Mixture of Fruit Waste and Chicken Intestinal Content as Composting Activators - Mardiyono, Mohammad Sholeh; Nugroho, Julius Dwi; Massora, Maria (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2024)
The fermentation of fruit waste can produce bio-enzymes. These bio-enzymes may act as composting activators for composting organic materials. This study compared composting activators made from fruit waste, fruit waste enriched with chicken intestinal content, and Effective Microorganism-4 (EM-4) to evaluate their effectiveness for compost production. It was found that the peaks of temperatures of all activators applied were achieved within 3 days, varied between 55–57°C, and dropped to the lowest point on day 14 at a temperature of 33°C, indicating that the maturity of the compost fell in the same period. Based on statistical analysis, differences among the three activators were found in the C-organic and moisture content of the compost. However, the compost produced using the three activators, based on the quality standard determined by the Decree of Agriculture Minister of Republic Indonesia No. 261/KPTS/SR.310/6.M/4/2019 and SNI 19-7030-2004 were comparable and met these requirements. In conclusion, composting activators made from fruit waste and fruit waste enriched with chicken intestinal content might be used as composting activators for compost production as effective as composting activator EM-4.